Studi Biologi Hama Kutu Putih Pepaya Paracoccus marginatus Williams & Granara de Willink (Hemiptera: Pseudococadea) - Gregorius O Leta; Yustina Maria Silvia Wonga Puu; Imaculata Fatima (AGRICA, 2011)
The goal of this research was to understand the biology of P. marginatus, a common pest for papaya plants. This research used 1 type of treatment which was repeated 10 times. The results of this research were intended to illustrate the average development time of each development phase of P. marginatus. These phases were: the egg phase (6 days), the female nymph phase (10 days), the male nymph phase (17 days), female adult stage (11 days), male adult stage (3 days). On average, the female life cycle was 27 days, and the male life cycle was 26 days. On average, the pre-fertile stage lasted 4 days, the fertile stage lasted 6 days and the post fertile stage lasted 1 day. On average the pre-egg-laying adult stage lasted 4 days, the egg-laying adult stage lasted 6 days and the post-egg-laying stage lasted 1 day. After the egg-laying stage, the average fecundity of P. marginatus was 370 eggs per female and from these, a total of 350 offspring were hatched per individual. The ratio of surviving Descendents to reproductive couples of P. marginatus white lice was 9:1.